Investigating the negative fan behaviors of a branded collegiate basketball student section - Gordon, Brian; Arney, Jeremy (Journal of Amateur Sport, 2017)
Branded collegiate student sections (e.g., the Cameron Crazies at Duke University) have been identified as the most committed supporters of the team. The marketing benefits of these groups have been documented yet the potential negative consequences have gone unexplored in the literature. This study aimed to understand what types of behavior fans in this context engaged in, why they engaged in these actions, and attempts to link some of these observations to relevant theory on fan violence. A multiple method design was employed in order to obtain both breadth and depth of the phenomenon as well as for data triangulation. Ten members of a large, collegiate basketball fan group participated in in-depth, semi-structured interviews and extensive fieldwork of the fan group was conducted over the course of a season. Finally, 197 members of the same college basketball fan group responded to a survey questionnaire. The results of this study indicated there are negative consequences linked to the behavior of members of the branded student section. University officials should be aware of the potential danger of these branded student sections and strengthen relations and authority over these groups to minimize the likelihood of negative fan behavior.